2018
DOI: 10.3390/en11010241
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Interprovincial Cooperative Energy Saving in China: An Electricity Utilization Perspective

Abstract: Abstract:As the world faces great challenges from climate change and environmental pollution, China urgently requires energy saving, emission reduction, and carbon reduction programmes. However, the non-cooperative energy saving model (NCESM), the simple regulation mode that is China's main model for energy saving, is not beneficial for optimization of energy and resource distribution, and cannot effectively motivate energy saving at the provincial level. Therefore, we propose an interprovincial cooperative en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 108 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…To this context, cooperative game theory could be used to improve the traditional SPM, and the Shapley value is used to solve the improved spatial proportional allocation index. The expected incremental cost that pipeline produces when laid into utility tunnel is the basis for the Shapley value-based cost allocation method, ensuring that the allocation solution is fair and desirable [16]. Since the order that the pipelines laid into the utility tunnel affects the incremental cost produced, the Shapley value considers all orders equally and gives them equal weights.…”
Section: Improved Spatial Proportional Methods Based On Shapley Valuementioning
confidence: 99%
“…To this context, cooperative game theory could be used to improve the traditional SPM, and the Shapley value is used to solve the improved spatial proportional allocation index. The expected incremental cost that pipeline produces when laid into utility tunnel is the basis for the Shapley value-based cost allocation method, ensuring that the allocation solution is fair and desirable [16]. Since the order that the pipelines laid into the utility tunnel affects the incremental cost produced, the Shapley value considers all orders equally and gives them equal weights.…”
Section: Improved Spatial Proportional Methods Based On Shapley Valuementioning
confidence: 99%
“…In game theory, Nash equilibrium is a fundamental concept and the most widely used technique for cooperative and non-cooperative game models to find the sizing and outcome of decision variables [35]. Shapley values is a technique mostly used for cooperative game models to fairly allocate the benefits among the independent power producers for the success of cooperation [24,36]. In this research, cooperative game models are designed using a technique of Nash equilibrium for optimum sizing of the capacities of generation resources and batteries.…”
Section: Game Theory Techniques and Algorithmmentioning
confidence: 99%
“…Ang assessed 104 studies from 2001 to 2014 and found that availability, affordability, and energy efficiency were the key focus areas [36]. Since climate change issues and air pollution damage have become of greater concern, the environmental sustainability of energy systems has become a key objective for secure energy futures [37][38][39]. Energy supply security and energy sustainability are not in conflict.…”
Section: Definition Of Energy Supply Securitymentioning
confidence: 99%